Custos de funcionamento das unidades federativas brasileiras e suas implicaç\~oes sobre a criaç\~ao de novos estados - Rogério Boueri (Instituto de Pesquisa Econômica Aplicada (IPEA), 2008)
– This paper tried to evaluate the increasing of the federative public spending associated with the creation of a new State within the Brazilian Federation. The estimates pointed out that each new State increases the federative expenditure by R 832 millions. It was also estimated that Brazilian States expend, in average, R 564,69 with each citizen and that each Real produced in an Brazilian State requires a State expenditure of 7,5 cents of Real. It was also found that the State's area and the number of municipalities contained in a State do not show any correlation with the State expenditure.
Keywords: H07; H11; H05; 330